Optimalisasi temperatur kalsinasi untuk mendapatkan kalsit-CaCO3 dalam cangkang pensi (Corbicula moltkiana) yang terdapat di Danau Maninjau (Optimization of calcination temperature to obtain calcite-CaCO3 in pensi shells (Corbicula moltkiana) found in Lake Maninjau) - Suci Wahyuni; Yenni Darvina; - Ramli (PILLAR OF PHYSICS, 2015)
The utilization of pensi (Corbicula moltkiana) shell waste in Maninjau lake is not optimal so that we need an effort to make it has economic value. One of them is using calcium carbonate in pensi shell. Calcite is one of calcium carbonate polymorphs are often used in industrial paint, paper, ink, and other chemical industries. This experiment aims to determine optimum of calcination temperature to obtain calcite in pensi shell can be exploited and has economic value. The method that used is by giving calcination temperature of 300˚C, 320˚C, 340˚C, 360˚C, 380˚C, dan 400˚C to pensi shell and then characterized using XRF and XRD. Result of characterization using XRF show that pensi shell containe calcium element is 93,207% dan about 6% of other elements such as Si, Al, Ag, Mg, P, dan Fe. The result of characterizaion using XRD that compared with the ICDD database show that calcite phase has Rombhohedral structure with unit cell a = 4,9590Å, b = 7.9680Å, and c = 5.4710Å. Based of analysis can be concluded that the increase in temperature causes increasing intensity of calcite and dominant temperature to obtaine calcite phase at 400˚C